Novel NRF2‐activated cancer treatments utilizing synthetic lethality. Issue 12 (18th October 2022) - Baird, Liam; Kensler, Thomas W.; Yamamoto, Masayuki
Abstract: The KEAP1‐NRF2 pathway regulates the main inducible cellular response to oxidative and electrophilic stresses. Activating mutations in the KEAP1‐NRF2 pathway occur commonly in human cancer, where they contribute to the formation of aggressive tumours that are associated with a poor prognosis for patients. An important clinical feature of these tumours is their defiance to all current anti‐cancer treatment regimens, highlighting the need for the development of new therapeutic strategies to target NRF2‐activated cancers. In this review, we discuss the mechanisms through which acquired NRF2 hyperactivation can result in resistance of tumours to immune checkpoint inhibitor therapies in addition to classical chemotherapeutics, and propose with examples that using a synthetic lethal strategy mediated by NRF2‐target gene‐dependent bioactivation of prodrugs represents a promising strategy to specifically enhance toxicity to heretofore untreatable NRF2‐hyperactivated human tumours.